Perbedaan Perilaku Masyarakat tentang Pengelolaan Sampah Rumah Tangga Terhadap Pemberian Penyuluhan - Nurhayati Nurhayati; Oktavianis Oktavianis; Cici Apriza Y; Budi Dwi Satria (Jurnal Sosiologi Andalas, 2020)
Looking at population growth in Indonesia, it certainly has a significant effect on the issue of waste generation, where the number of wastegeneration from 2015-2019 has always increased, as well as Tanah Datar District, which has a large amount of waste generation, reaching 133.66 ton per day. Therefore, counseling is an important effort to do in order to manage household waste. The purpose of this study was to look at The Effectiveness of Counselling on Community Behavior Related to Household Waste Management in Kenagarian Baringin Tanah Datar. This study used Quasi Experiment Design method. The samples were 16 respondents. They were divided into 2 groups. The first group was given counseling through audio visual media and the other given counseling through leaflet media. The data were collected through questionnaire. Then, it was processed by reducing, presenting and drawing conclusions. Last, the data were analyzed by Paired Sample T Test and the Independent T-Test. The results of this study showed that the audio visual and leaflet media were increase respondents’ knowledge (p = 0.0005 and 0.0005), attitudes (p = 0.0005 and 0.0005) and actions (p = 0.0005 and 0,0005). Moreover, there was no difference increasing of mean of the knowledge, attitudes and actions of audio visual media group with the leaflet media group (p = 0.751, 0.519 and 0.727). In short, it can be concluded that audio visual media and leaflets were effective for health promotion. Then, it is suggested to the public always manage household waste properly. Next, it is better for the health workers to provide counseling and supervision of environmental health on a regular basis.